2007
DOI: 10.1002/ajhb.20637
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in growth and nutrition in a sample of rural ontario schoolchildren

Abstract: This paper reports findings of a cross-sectional study of the growth and nutrition of children living in rural Ontario, Canada. The objectives of the research were threefold:(1) to obtain data on obesity prevalence and nutrient intake in a sample of rural Canadian schoolchildren, (2) to compare findings with rural and national-level data on obesity prevalence and nutrient intake, and (3) to provide data to school board and public health agencies planning and implementing nutrition policy and programs to this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 76 publications
(111 reference statements)
6
15
0
Order By: Relevance
“…This finding is consistent with two other studies conducted in Canada and England [8,9]. The higher intake of these micronutrients could be related to the overall higher dietary intake among boys in this age range [8,9,33]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with two other studies conducted in Canada and England [8,9]. The higher intake of these micronutrients could be related to the overall higher dietary intake among boys in this age range [8,9,33]. …”
Section: Discussionsupporting
confidence: 92%
“…A Canadian and a British study reported inadequacies in micronutrient intake in girls age 7–13 years having lower intakes of numerous micronutrients compared to boys [8,9]. Bailey et al, using 2003–2006 NHANES data, found micronutrient inadequacies in children older than 8 years, which were improved by use of dietary supplements for most, but not all, micronutrients (vitamin D and calcium remained low) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Given our prior findings in female overeater populations (Levitan et al, 2004, Kaplan et al, 2008, Levitan et al, 2006), and significant evidence for sex differences in eating behaviour and obesity (Cooke and Wardle, 2005, Galloway, 2007), as well as for brain reward processes (Hurd et al, 1999, Adinoff et al, 2003), we hypothesized that different relationships between the 7R allele and eating behaviour would emerge in girls and boys i.e. that only girls carrying the 7R allele would exihibit preference for highly palatable, highly caloric foods (rich in fat and/or sugar).…”
Section: Introductionmentioning
confidence: 59%
“…By incorporating micronutrient health variables in their research in addition to more conventional variables such as energy and anthropometric measurements, human biologists and anthropologists are increasingly contributing to human ecological nutrition, health, and reproduction (e.g. Fujita et al, 2011Fujita et al, , 2012Galloway, 2007;Gittelsohn et al, 1997;Jamieson et al, 2012;Kuhnlein et al, 1997;Miller, 2010;Shell-Duncan and McDade, 2005;Wander et al, 2009). Micronutrient intake or status assessment, however, is often invasive, logistically challenging, and cost prohibitive in field-based studies with anthropological populations.…”
Section: Discussionmentioning
confidence: 98%